Testing the Importance of Search Frictions, Matching, and Reservation Prestige through Randomized Experiments in Jordan - Groh, Matthew (World Bank Group, Washington, DC, 2014)
Unemployment rates for tertiary-educated youth in Jordan are high, as is the duration of unemployment. Two randomized experiments in Jordan were used to test different theories that may explain this phenomenon. The first experiment tested the role of search and matching frictions by providing firms and job candidates with an intensive screening and matching service based on educational backgrounds and psychometric assessments. Although more than 1,000 matches were made, youth rejected the opportunity to even have an interview in 28 percent of cases, and when a job offer was received, they rejected this offer or quickly quit the job 83 percent of the time. A second experiment built on the first by examining the willingness of educated, unemployed youth to apply for jobs of varying levels of prestige. Youth applied to only a small proportion of the job openings they were told about, with application rates higher for higher prestige jobs than lower prestige jobs. Youth failed to show up for the majority of interviews scheduled for low prestige jobs. The results suggest that reservation prestige is an important factor underlying the unemployment of educated Jordanian youth.